2010
DOI: 10.4103/1817-1745.66671
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiologic findings in children with spastic cerebral palsy

Abstract: Context:Cerebral palsy (CP) is a heterogeneous group of permanent, non-progressive motor disorders of movement and posture caused by chronic brain injuries. It is the most common cause of physical disability in childhood; spastic cerebral palsy being the most prevalent of its various forms. There is scanty information about the neurophysiologic investigations in children diagnosed as having spastic CP.Aims:The aim of the study was to investigate the relationship between abnormal VEP and BAEP findings with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
(9 reference statements)
0
6
0
1
Order By: Relevance
“…The interpeak latency of waves III-V of brainstem auditory evoked potential (BAEP) reflects activities of the brainstem auditory pathway and the influence of activities of structures surrounding the pathway. It is said that BAEP are reliable in predicting the outcome of patients with severe brain damage [19,20]. Our studies found that there were no responses of BAEP or the interpeak latency of waves III- Fig.…”
Section: Discussionmentioning
confidence: 91%
“…The interpeak latency of waves III-V of brainstem auditory evoked potential (BAEP) reflects activities of the brainstem auditory pathway and the influence of activities of structures surrounding the pathway. It is said that BAEP are reliable in predicting the outcome of patients with severe brain damage [19,20]. Our studies found that there were no responses of BAEP or the interpeak latency of waves III- Fig.…”
Section: Discussionmentioning
confidence: 91%
“…1 It is well known that brain damage is associated with lack of coordination of voluntary muscles, restricted balance performance, gait deviations, and poor postural control of movement. Postural control is fundamental for the efficient performance of all activities of daily living.…”
mentioning
confidence: 99%
“…При оценке АСВП у 80 детей в возрасте 3-12 лет в ряде случаев регистрировалось выпадение отдельных пиков, удлинение межпиковой латентности N 1 -N 5 и редукция высоты N 5 пика у детей с тяжелой асфиксией в анамнезе, что в совокупности отражает дизафферентацию преимущественно за счет межъядерной десинхронизации на уровне ствола головного мозга при сохранной миелинизации проводникового отдела анализатора у большинства пациентов с ЦП [17]. В то же время анализ параметров АСВП у 50 детей в возрасте от 4 мес до 10 лет выявил сочетанное статистически значимое увеличение как латентности основных пиков, так и межпиковых латентностей по сравнению с показателями контрольной группы, что говорит о смешанном патогенезе нарушения акустической афферентации [18].…”
Section: оригинальные исследованияunclassified